UPDATE MANAGEMENT CONCURRENT INFECTION BETWEEN DENGUE VIRAL AND SALMONELLA - Wikanesthi, Dyah; Sari, Desiana W; Chilvia, Eva; Soedirham, Oedojo; Kurniasari, Lely; Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2014)
Since Januari 2013, Soerya Hospital has found many cases with positive result of IgM Salmonella along with NS1 or IgM & IgG Dengue. The clinical manifestations mostly are high fever, headache, vomiting, malaise and plasma leakage. Some of them with convulsion and unconsciousness. Therefore in order to get well of care management, this clinical phenomena should be studied carefully. The aim of this research is to get update management concurent Dengue Viral and Salmonella infection. Observational study had been done, since Januari 2013 until Juli 2013. Purposive sampling in 30 case of concurent Dengue Viral and Salmonella infection compared with 30 case of Dengue Viral infection alone. Diagnosis has published based on WHO 2011 criteria. By using anti vomiting drug, anti pyretic, anti convulsion and antibiotic for Salmonella infection and rehidration using Ringer Acetate, combining Ringer Asetat andDextrose 5% or combining Ringer Asetat Saline 0,225% or solution of Dextrose 5% and Saline 0,45 during 4–5 days hospitalization. The result show that all cases were recovered and got well. There is no significant different between concurent Dengue Viral and Salmonella infection compared with Dengue Viral infection alone. Some cases showed that length time to stay in hospital become1–2 days longer. It was due to delayed getting antibiotic for Salmonella infection. All cases had got first drugs accurately in a clinical manifestation that has been daily showed. It was as a problem solving for saving all the cases.